Species : new interdisciplinary essays - Wilson, Robert A. (Robert Andrew) (Cambridge, Mass. : MIT Press, 1999)
This fresh collection of essays, drawn from a broad range of disciplines, brings neglected cognitive, anthropological, and historical dimensions to philosophical debates over species.
1. On the impossibility of a monistic account of species / by John Dupré -- 2. On the plurality of species: questioning the party line / by David L. Hull -- 3. The general lineage concept of species and the defining properties of the species category / by Kevin de Queiroz -- 4. When is a rose?: the kinds of tetrahymena / by David L. Nanney -- 5. Species as ecological mosaics / by Kim Sterelny -- 6. Homeostasis, species, and higher taxa / by Richard Boyd -- 7. Realism, essence, and kind: resuscitating species essentialism? / by robert a. wilson -- 8. squaring the circle: natural kinds with historical essences / by Paul E. Griffiths -- 9. The universal primacy of generic species in folkbiological taxonomy: implications for human biological, cultural, and scientific evolution / by Scott Atran -- 10. Species, stuff, and patterns of causation / by Frank C. Keil and Daniel C. Richardson -- 11. Species and the linnaean hierarchy / by Marc Ereshefsky -- 12. Getting rid of species? / by Brent D. Mishler.
"A Bradford book."
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Species -- Philosophy; Espèces (Biologie) -- Philosophie; SCIENCE -- Life Sciences -- Evolution; Species -- Philosophy; Art; Biologie; Naturwissenschaften; Philosophie; Aufsatzsammlung; Soorten (biologie); Filosofische aspecten; Ecology; Earth & Environmental Sciences; Espèces (biologie)